Effect of photooxidative ageing at natural conditions on dynamic mechanical properties of PE-LD/PE-LLD blends - Ribes-Greus, A. (Polimery, 2009)
The blends of low density polyethylene with linear low density polyethylene and pure polyolefins were blown for their use in agriculture. These films were stabilized with a commercial Hindered Amine Light Stabilized (HALS). Blends with this stabilizer were photodegraded under natural outdoor weathering conditions during two years. Photodegradation involves oxidation of the polymer chain and causes modifications of the mechanical properties of the exposed films that were monitored by dynamic mechanical spectroscopy. The mechanical relaxation spectra show the alfa, beta and gamma relaxation zones, in decreasing order of temperature. Their characterization was carried out using the deconvolution method proposed by Charlesworth, together with the Fuoss-Kirkwood equation. The results obtained for pure PE-LLD and PE-LD and their blends show that the storage modulus increases as a function of the exposure time. The maximum storage modulus is reached at different exposure times depending on the blend composition. The beta relaxation zone is the most affected by weathering. A new relaxation was detected between -85° and -75°, which was modified as a function of the exposure time, and finally even disappeared. All the samples exhibit the same evolution, but at different time scales. It has been found that after two years of exposure, the degradation of the interfacial region is already initiated. The blends with 50% of PE-LD are the most resistant to weathering.